2017
DOI: 10.1038/s41598-017-02258-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing Leymus chinensis with whole-crop wheat hay on Holstein bull apparent digestibility, plasma parameters, rumen fermentation, and microbiota

Abstract: Twelve Holstein bulls were used in a 4 × 4 Latin square design to investigate the effects of using whole-crop wheat hay (WCWH) as a substitute for Leymus chinensis (LC) on apparent digestibility, plasma parameters, ruminal fermentation, and microbial communities. Experimental treatments were four proportions of WCWH, 0, 33, 67, and 100%, as a substitute for LC (WCWH0, WCWH33, WCWH67, and WCWH100, respectively). The WCWH100 group showed a higher nutritional intake of crude protein (CP) and higher apparent diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 73 publications
4
31
0
Order By: Relevance
“…In this study, albumin, cholesterol, glucose, total protein and urea N differed among fattening phases because of generally physiological reasons, which are consistent with the reports of Mohri et al [24]. The urea N is the main end-product of protein hydrolysis and amino acid metabolism [25], and its concentration has shown to be positively associated with intake of CP [12]. Therefore, it was reasonable that plasma urea N increased as dietary nutrient density increased as a result of increased CP intake.…”
Section: Digestive and Physiological Characteristicssupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, albumin, cholesterol, glucose, total protein and urea N differed among fattening phases because of generally physiological reasons, which are consistent with the reports of Mohri et al [24]. The urea N is the main end-product of protein hydrolysis and amino acid metabolism [25], and its concentration has shown to be positively associated with intake of CP [12]. Therefore, it was reasonable that plasma urea N increased as dietary nutrient density increased as a result of increased CP intake.…”
Section: Digestive and Physiological Characteristicssupporting
confidence: 91%
“…It has also been suggested that odd branched-chain fatty acids could be synthesized by elongating propionate [41]. Hence, it is reasonable to observe positive correlation between Succiniclasticum abundance and concentrations of propionate, isovalerate, valerate, and total BCVFA due to vital roles of this genus in fermenting succinate to propionate and degradation of protein [12,40].…”
Section: Correlations Between Ambient Temperature Physiological and mentioning
confidence: 98%
See 2 more Smart Citations
“…Bacteroidetes , Firmicutes and Proteobacteria were the most abundant phylum in this study. These are the main bacterial phyla, and they play vital roles in rumen fermentation [38,39]. Jami and Mizrahi [40] reported that the proportion of Bacteroidetes was higher than Firmicutes , which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%